2005
DOI: 10.1021/jm049060w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Topoisomerase I Poisoning by Lamellarins:  Comparison with Camptothecin and Structure−Activity Relationships

Abstract: A series of lamellarin derivatives have been studied as topoisomerase I (Top1) inhibitors. Molecular models of the ternary complexes formed between the DNA-Top1 ensemble and lamellarin D (LMD) or camptothecin (CPT) fully intercalated into the duplex DNA have been built and studied by means of nanosecond molecular dynamics simulations in aqueous solution. Our results show that the 20-OH and 8-OH of LMD can participate in hydrogen-bonding interactions with the side chains of Glu356 and Asn722, respectively, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(138 citation statements)
references
References 43 publications
5
133
0
Order By: Relevance
“…The results are summarized in Table 3. [8] and leukemia cells [37]. Several molecular targets have been described for Lam-D and other lamellarins.…”
Section: Activity and Mechanism Of Actionmentioning
confidence: 99%
“…The results are summarized in Table 3. [8] and leukemia cells [37]. Several molecular targets have been described for Lam-D and other lamellarins.…”
Section: Activity and Mechanism Of Actionmentioning
confidence: 99%
“…Selected structures of lamellarins isolated from ascidians Following the discovery of the potent anti-proliferative and proapoptotic activities of lamellarins, their biological activities have been extensively studied, in particular their capacities to interfere with topoisomerase (TOPO) I and mitochondria, both contributing to their potent cytotoxicity. Although all the aspects of the lamellarins' mechanism of action are not completely known, it has been demonstrated that they are potent inhibitors of topoisomerase (TOPO) I, they interact with DNA, they target mitochondria directly, and they induce the release of cytochrome C and apoptosis-inducing factor (AIF) [51,[53][54][55][56][57][58]. Lamellarin D (81) was identified as a potent TOPO I poison in 2003 [53]; it binds relatively weakly to DNA, presumably via the insertion of its planar pentacyclic chromophore between DNA base pairs.…”
Section: Bis-steroidal Pyrazines: Ritterazines and Cephalostatins Pomentioning
confidence: 99%
“…Lamellarin D (81) was identified as a potent TOPO I poison in 2003 [53]; it binds relatively weakly to DNA, presumably via the insertion of its planar pentacyclic chromophore between DNA base pairs. Intercalation of the flat chromophore between two adjacent base pairs exposes the perpendicular methoxyphenol moiety toward the major groove of DNA where the enzyme can be trapped [54,55]. This DNA interaction, although relatively weak, provides the necessary anchorage for stabilization of the enzyme-DNA complex.…”
Section: Bis-steroidal Pyrazines: Ritterazines and Cephalostatins Pomentioning
confidence: 99%
“…in 1985. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] These lamellarins exhibit a number of interesting biological activities such as potent cytotoxicity against cancer cell lines, 8,9,11,12,[14][15][16][17][18][19][20][21] multi-drug resistance (MDR) reversal activity, 15,16 anti-HIV activity, 11,18,22 topoisomerase I inhibitory activity, 23,24 inhibition of mitochondrial function, [25][26][27][28] and protein kinases inhibitory activity. 29 Lamellarins possess a unique 14-phenyl-6H- [1]benzopyrano- According to X-ray crystallographic analyses of several lamellarins, the aryl group attached to C1 is This paper is dedicated to Professor Dr. Victor Snieckus on the occasion of his 77 th birthday.…”
Section: Up To Now Approximately Fifty Lamellarins Have Been Charactmentioning
confidence: 99%